Total Phenolic Content and Antioxidant Activity of Some Malvaceae Family Species - Adriana Maria Fernandes de Oliveira; Lilian Sousa Pinheiro; Charlane Kelly Souto Pereira; Wemerson Neves Matias; Roosevelt Albuquerque Gomes; Otemberg Souza Chaves; Maria de Fátima Vanderlei de Souza; Reinaldo Nóbrega de Almeida; Temilce Simões de Assis (MDPI AG, 2012)
The antioxidant activity of four species of the Malvaceae family (Sidastrum micranthum (A. St.-Hil.) Fryxell, Wissadula periplocifolia (L.) C. Presl, Sida rhombifolia (L.) E. H. L and Herissantia crispa L. (Brizicky)) were studied using the total phenolic content, DPPH radical scavenging activity and Trolox equivalent antioxidant capacity (TEAC) assays. The antioxidant activity of the crude extract, phases and two isolated flavonoids, kaempferol 3,7-di-O-α-l-rhamnopyranoside (lespedin) and kaempferol 3-O-β-d-(6''-E-p-coumaroil) glucopyranoside (tiliroside) was determined. The results showed that there is a strong correlation between total polyphenol contents and antioxidant activity of the crude extract of Sidastrum micranthum and Wissadula periplocifolia; however, this was not observed between Sida rhombifolia and Herissantia crispa. The ethyl acetate (EaF) phase showed the best antioxidant effect in the total phenolics, DPPH and TEAC assays, followed by the chloroform (CfF) phase, in most species tested. Lespedin, isolated from the EaF phase of W. periplocifolia and H. crispa may not be responsible for the antioxidant activity due to its low antioxidant activity (IC50: DPPH: 1,019.92 ± 68.99 mg/mL; TEAC: 52.70 ± 0.47 mg/mL); whereas tiliroside, isolated from W. periplocifolia, H. crispa and S. micrantum presented a low IC50 value (1.63 ± 0.86 mg/mL) compared to ascorbic acid in the TEAC assay.